2004
DOI: 10.1007/s00431-004-1580-0
|View full text |Cite
|
Sign up to set email alerts
|

Severe respiratory syncytial virus bronchiolitis in children: from short mechanical ventilation to extracorporeal membrane oxygenation

Abstract: The data suggest that gestational age, requirement of neonatal oxygen supplementation, bronchopulmonary dysplasia and tracheal colonisation with Haemophilus influenzae are correlated with prolonged mechanical ventilation in children with bronchiolitis. Only bronchopulmonary dysplasia was associated with a need for extracorporeal membrane oxygenation that may provide lifesaving support in infants refractory to conventional management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 21 publications
1
36
0
3
Order By: Relevance
“…For infants who are admitted to the ICU with RSV infection and require mechanical ventilation, Prodhan et al [98,99] listed several risk factors for prolonged mechanical ventilation (>8 days). Using various variables including some collected during the first two days after intubation, Prodhan et al [98] built a logistic regression model to predict prolonged mechanical ventilation, with a large AUC of 92% and a reasonably good accuracy of 84%.…”
Section: Predicting Prolonged Mechanical Ventilationmentioning
confidence: 99%
See 2 more Smart Citations
“…For infants who are admitted to the ICU with RSV infection and require mechanical ventilation, Prodhan et al [98,99] listed several risk factors for prolonged mechanical ventilation (>8 days). Using various variables including some collected during the first two days after intubation, Prodhan et al [98] built a logistic regression model to predict prolonged mechanical ventilation, with a large AUC of 92% and a reasonably good accuracy of 84%.…”
Section: Predicting Prolonged Mechanical Ventilationmentioning
confidence: 99%
“…Among ventilated children with RSV bronchiolitis in the ICU, 9.3% of them will fail mechanical ventilation, develop profound hypoxemia, and need extracorporeal membrane oxygenation support [99]. For ventilated infants with RSV bronchiolitis in the ICU, Flamant et al [99] identified chronic lung disease as a predictor of using extracorporeal membrane oxygenation.…”
Section: Predicting the Use Of Extracorporeal Membrane Oxygenationmentioning
confidence: 99%
See 1 more Smart Citation
“…Postoperativ blieb das Mädchen über 9 Tage intubiert. Die bakterielle Superinfektion [19] und auch die Atelektasenbildung [20] passen zu einer längeren Beatmungsdauer.…”
Section: Risikoeinschätzungunclassified
“…Além disso, os grupos com doença cardíaca congênita ou doença pulmonar crônica apresentam duração maior da terapêutica de oxigenação suplementar (Flamant et al, 2005).…”
Section: Página 31unclassified